The Kiai’s Cultural Strategy in Shaping the Religious Culture of the Community of Temboro Magetan Village, East Java - Zainal Arifin; Maragustam Maragustam; Muqowim Muqowim; Hafidh 'Aziz (Dinamika Ilmu, 2021)
Religious culture in the village of Temboro, which made it is known as "Kampung Madinah", certainly did not happen suddenly, but there was a process of formation and role of Kiai and Pesantren Al-Fatah. This study aims to analyze the Kiai’s cultural strategy in developing a religious culture using a phenomenological approach and collects data through in-depth interviews, active participant observation, and documentation. The study results show that, firstly, ideological culture is the strategy of the Kiai in shaping the religious culture of the Temboro community. Secondly, the ideological culture of the Tablighi Jamaat has an impact on changing the five religious cultures of the Temboro community, namely: (1) ideological faith, (2) normative Islam, (3) Sufistic religious experience, (4) moderate-textual religious knowledge, (5) Maqami-intiqali practice.